2018
DOI: 10.3389/fphys.2018.01484
|View full text |Cite
|
Sign up to set email alerts
|

A Ciliary Protein EVC2/LIMBIN Plays a Critical Role in the Skull Base for Mid-Facial Development

Abstract: Ellis-van Creveld (EvC) syndrome is an autosomal recessive chondrodysplastic disorder. Affected patients present a wide spectrum of symptoms including short stature, postaxial polydactyly, and dental abnormalities. We previously disrupted Evc2, one of the causative genes for EvC syndrome, in mice using a neural crest-specific, Cre-mediated approach (i.e., P0-Cre, referred to as Evc2 P0 mutants). Despite the fact that P0-Cre predominantly targets the mid-facial region, we reported that many mid-facial defects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…6 , Supplementary Tables 21 – 23 ). Importantly, the key phenotypes that are often used to describe pronounced differences in facial shape between humans and chimpanzees (specifically, midfacial retrusion with a more downward facial trajectory 1 ) are observed in both the current and previous Evc2 KO studies 64 , 65 , 68 , as well as in Ellis-van Creveld patients 47 , 65 ( Fig. 6 , Extended Data Fig.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…6 , Supplementary Tables 21 – 23 ). Importantly, the key phenotypes that are often used to describe pronounced differences in facial shape between humans and chimpanzees (specifically, midfacial retrusion with a more downward facial trajectory 1 ) are observed in both the current and previous Evc2 KO studies 64 , 65 , 68 , as well as in Ellis-van Creveld patients 47 , 65 ( Fig. 6 , Extended Data Fig.…”
Section: Resultsmentioning
confidence: 61%
“…Studies in cattle and mice have shown that the role of EVC2 is conserved in these mammals 55 , 63 68 . In humans, homozygous loss-of-function mutations in either EVC2 or EVC cause the Ellis-van Creveld syndrome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many elements within the craniofacial region, specifically the neurocranium and viscerocranium, arise from neural crest cells (NCCs), a special population of cells that maintain their identity despite divergence from the ectoderm in early gastrulation [52]. Abnormal craniofacial morphology (i.e., midfacial depression) in both global and NCC-specific Evc2/Limbin deficient mice (referred to as Evc2/Limbin-KO and Evc2/Limbin-cKO, respectively) is a consequence of abnormalities within NCC-derived elements of the neurocranium and viscerocranium [50,51,53,54]. As with patients with EVC, midfacial depression or retrusion in mice becomes more pronounced with age and can be attributed to positional differences between the nasal bone, jaws, and cranial base [51,53].…”
Section: Craniofacial Phenotypementioning
confidence: 99%
“…Abnormal craniofacial morphology (i.e., midfacial depression) in both global and NCC-specific Evc2/Limbin deficient mice (referred to as Evc2/Limbin-KO and Evc2/Limbin-cKO, respectively) is a consequence of abnormalities within NCC-derived elements of the neurocranium and viscerocranium [50,51,53,54]. As with patients with EVC, midfacial depression or retrusion in mice becomes more pronounced with age and can be attributed to positional differences between the nasal bone, jaws, and cranial base [51,53]. Though this suggests a critical, NCC-specific role for Evc2/Limbin in determining postnatal craniofacial morphology, it does not indicate which structure (i.e., maxilla vs. skull base) is responsible for the resultant phenotype.…”
Section: Craniofacial Phenotypementioning
confidence: 99%